1981
DOI: 10.1111/j.1751-1097.1981.tb05329.x
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Water at the Retinal Binding Site in Rhodopsin and Early Light‐induced Intramolecular Proton Transfer

Abstract: Extensive dehydration of air‐dried films of bovine rod outer segment membranes induces fully reversible changes in the absorption spectrum of rhodopsin, indicative of deprotonation of the retinylidene Schiff base in more than 50% of the rhodopsin molecules in the sample. This suggests that water is involved at the site of the Schiff base protonation in rhodopsin. In contrast, the spectrum of metarhodopsin I is resistant to similar dehydrating conditions, implying a significant difference in the mechanism for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…It has been observed that removal of water molecules from the Schiff base pocket can result in displacement of positive charge away from the Schiff base nitrogen, leading to deprotonation of the Schiff base (Rafferty and Shichi, 1981;Deng et al, 1994;Harosi and Sandorfy, 1995;Nagata et al, 1997). Thus, some (or all) of the eight critical amino acids in the UV pigments may eliminate water molecules in the Schiff base pocket.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that removal of water molecules from the Schiff base pocket can result in displacement of positive charge away from the Schiff base nitrogen, leading to deprotonation of the Schiff base (Rafferty and Shichi, 1981;Deng et al, 1994;Harosi and Sandorfy, 1995;Nagata et al, 1997). Thus, some (or all) of the eight critical amino acids in the UV pigments may eliminate water molecules in the Schiff base pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intramembranous accessibility to external small molecules and water is required for Rho activation to advance beyond the Meta I state (26,27). Moreover, the retinylidene chromophore becomes accessible to reagents such as NH 2 OH or NaBH 4 only upon attainment of the Meta II state (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Structural water forming hydrogen bonds from the PSB to O 2 of Glu-113 (not shown in Fig. 3) is likely to be present (7,42).…”
Section: Scheme IIImentioning
confidence: 99%
“…The distance of the Glu-113 oxygen closest to C12 (referred to as O1) was kept at 3 Å in rho and in batho (7,41). It is likely that structural water forms a hydrogen bond network from O2 of Glu-113 to the SB proton (white) (not shown in this figure) (7,42). In rho, the distances of the SB proton to O2 of Glu-113 in the dark state, batho, bsi, and lumi are 4.6, 4.4, 3.6, and 3.9 Å, respectively.…”
Section: Scheme IIImentioning
confidence: 99%